The repertoire of heavy chain immunoglobulin genes in B‑cell chronic lymphocytic leukemia in Russia and Belarus - B. V. Biderman; E. A. Nikitin; T. F. Sergienko; A. V. Bakun; L. B. Taras; A. I. Svirnovskiy; A. B. Sudarikov (Онкогематология)
Mutation status of the heavy chain variable region genes has long been known as an important factor in long‑term prognosis in B‑cell chronic lymphocytic leukemia (B‑CLL). A more detailed study of the gene sequences of immunoglobulin heavy chain (IgVH) led to the discovery of stereotyped antigen receptors (SAR) — receptors that have the same set of VH‑, D‑ and JH‑genes used. Cells with SARs have been found almost in a quarter of all B‑CLL cases. This phenomenon is not observed in other lymphatic tumors. In our study, we confirmed and extended the basic observations concerning the repertoire of IgVH in B‑CLL. Differences in the B‑CLL IgVH gene repertoirs between Russia, Вelarus and other countries are also analysed and discussed.